New Oral Anticoagulants vs. Vitamin K Antagonists Among Patients With Cardiac Amyloidosis: Prognostic Impact - Cariou, Eve; Sanchis, Kevin; Rguez, Khailène; Blanchard, Virginie; Cazalbou, Stephanie; Fournier, Pauline; Huart, Antoine; Roussel, Murielle; Cintas, Pascal; Galinier, Michel; Carrié, Didier; Maury, Philippe; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial arrhythmia (AA) is common among patients with cardiac amyloidosis (CA), who have an increased risk of intracardiac thrombus. The aim of this study was to explore the prognostic impact of vitamin K-antagonists (VKA) and direct oral anticoagulants (DOAC) in patients with CA. Methods and Results: 273 patients with CA and history of AA with long term anticoagulation−69 (25%) light chain amyloidosis (AL), 179 (66%) wild-type transthyretin amyloidosis (ATTRwt) and 25 (9%) variant transthyretin amyloidosis (ATTRv)–were retrospectively included between January 2012 and July 2020. 147 (54%) and 126 (46%) patients received VKA and DOAC, respectively. Patient receiving VKA were more likely to have AL with renal dysfunction, higher NT-proBNP and troponin levels. Patients with ATTRwt were more likely to receive DOAC therapy. There were more bleeding complications among patients with VKA (20 versus 10%; P = 0.013) but no difference for stroke events (4 vs. 2%; P = 0.223), as compared to patients with DOAC. A total of 124 (45%) patients met the primary endpoint of all-cause mortality: 96 (65%) and 28 (22%) among patients with VKAs and DOACs, respectively (P < 0.001). After multivariate analysis including age and renal function, VKA was no longer associated with all-cause mortality. Conclusion: Among patients with CA and history of AA receiving oral anticoagulant, DOACs appear to be at least as effective and safe as VKAs.